Usain Bolt. A “hopeful monster”? A descriptive case study (Usain Bolt. Un "monstruo esperanzado"? Un estudio de caso descriptivo) - José Augusto Rodrigues dos Santos (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Usain Bolt's stunning sportive achievements sparked admiration from around the world and raised the question of the genesis of his sport excellence. In the light of the various theories of evolution, we try to understand whether there are evolutionary grounds for considering Usain Bolt a “hopeful monster”, i.e. a transgressive phenotype beyond the range of parental phenotypes. This hypothesis would call into question the gradualism defended by Darwin and would give room to saltationism by which profound changes can occur in one or a few generations. It seems that the saltational hypothesis is not scientifically adequate to justify Usain Bolt’s sport performance. Not knowing the genetic profile of Usain Bolt and his ancestors, we can hypothesize that his sporting excellence is the result of a given polymorphism or phenotypic changes induced by ecological determinants, among which training and nutrition stand out.We can admit that Usain Bolt is a rare case of developmental plasticity that enables his genome to generate a phenotype associated with a specific competence for sprinting.In the current state of scientific knowledge, there is no way to associate any polymorphism with performance in sporting events related to strength and speed but a challenging field is open for science. Aware of the difficulties in characterizing Usain Bolt, he is undoubtedly the result of an extraordinary combination of genetic and environmental factors.